(untitled) (Signifiances (Signifying), 2021)
This article deals with the first moment of semiogenesis, that enigmatic moment when a simply expressive fact prepares itself to become a sign. It is a process of polarization in which an expression, where meaning and the sensible are in one piece, mutually indistinguishable, becomes polarized in order to reveal the interdependent faces of a signifier and a signified. To conduct this study, we will use Merleau-Ponty’s conceptions of (i) the elaboration of the expressive fact, and (ii) the genesis of the first speech, either as the intersection and convergence of verbal gestures, or as the sum of differentiating acts.